Types and forms of teaching organization. - Usmanova Kh (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides an understanding of the forms of educational organization. Traditional form of educational organization. The lesson is the main organizational form of teaching. Requirements for the lesson. Lesson types and structure are widely covered. Ways to modernize lessons today. In the lesson, students’ educational activities are revealed.